Reported rationales for HPV vaccination vs. Non-vaccination among undergraduate and medical students in South Carolina. Issue 2 (17th February 2021) - Barrera, J.; Greene, S.; Petyak, E.; Kenneson, S.; McGill, E.; Howell, H.; Billing, D.; Taylor, S.; Ewing, A.; Cull, J.
Abstract: Objective : We sought to identify factors that influence Human Papillomavirus (HPV) vaccination rates in individuals at two higher education institutions in South Carolina (SC). Participants: We surveyed 1007 students with a mean age and standard deviation of 20.3 ± 3.3 from September 2018 to December 2018. Methods: Participants answered 13 questions, assessing HPV vaccination rates, demographics, and rationales for vaccination vs. non-vaccination. Results: Of 1007 respondents, 700 received HPV vaccination, 165 were unvaccinated, 75 received partial vaccination and 138 were uncertain. Commonalities in HPV vaccination existed between females ( p = 0.037), individuals who received standard childhood vaccinations ( p = 0.04), and those not native-born in SC ( p < 0.001). Of non-vaccinated individuals, 37% "never thought about vaccination, " 32% did not perceive a need for vaccination, and 31% reported vaccine safety as reasons for not receiving the vaccine. Conclusions: Promotion of HPV vaccination may benefit from targeting SC natives, males, and individuals who are under-vaccinated or unvaccinated.